1993
DOI: 10.1007/bf01439160
|View full text |Cite
|
Sign up to set email alerts
|

Transient product from distributions in queueing networks

Abstract: In this paper it is shown that a necessary and sufficiënt condition for a Markovian queueing network to have transient product form is that all queues are infmite server queues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…As detailed in Boucherie and Taylor (1993), ρ i (t), i = 1, 2, ..., n is the solution to the following linear differential equation:…”
Section: Detailed State Probability Distribution Of Infinite Servers mentioning
confidence: 99%
“…As detailed in Boucherie and Taylor (1993), ρ i (t), i = 1, 2, ..., n is the solution to the following linear differential equation:…”
Section: Detailed State Probability Distribution Of Infinite Servers mentioning
confidence: 99%
“…In some cases, even if the state space is large, special characteristics can be exploited to carry out an exact analysis. Such situations are limited in practice to networks of infinite server queues [4,14]. Consequently, we most often must settle for an approximate solution.…”
Section: Introductionmentioning
confidence: 99%
“…, c N satisfy (7), (8), and (9). Conversely, if P(n, t ) is of the form (10), then insertion in the forward equations (11) implies (7), (8), and (9).…”
Section: Model and Technical Lemmamentioning
confidence: 99%
“…[26] to queueing networks consisting of infinite-server queues in the more general context of Poisson arrival location models. In Boucherie and Taylor [8] , it is shown that the only single-routing queueing networks that have transient product-form distribution are networks of infinite server queues. For two particular clustering processes for polymers with a treelike structure that have reaction rates proportional to the size of the polymers, the transient distribution is shown to be of product form [10,11] .…”
Section: Reaction Network and Product Form In The Literaturementioning
confidence: 99%